2003
DOI: 10.2516/ogst:2003032
|View full text |Cite
|
Sign up to set email alerts
|

Genes Involved in the Degradation of Ether Fuels by Bacteria of the Mycobacterium/Rhodococcus Group

Abstract: Résumé -Gènes impliqués dans la dégradation des éthers carburants par des bactéries du groupeMycobacterium/Rhodococcus -Un cluster de gènes codant pour un système de monooxygénase à cytochrome P-450 impliqué dans l'utilisation de l'éthyl tertio butyl éther (ETBE) a été cloné chez Rhodococcus ruber IFP 2001. Ce cluster comprend ethR, un gène régulateur putatif de la famille des régulateurs transcriptionnels araC/xylS ; ethA, codant pour une ferrédoxine réductase ; ethB, codant pour un cytochrome P-450 ; ethC, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…It is likely that the flanking transposon elements were the cause for high mobility. In principle, during the recombination event the excision of the eth genes results in a circular structure, which can then integrate into other genomes (7,8). Invading transposons are major agents of interspecies gene transfer (27).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is likely that the flanking transposon elements were the cause for high mobility. In principle, during the recombination event the excision of the eth genes results in a circular structure, which can then integrate into other genomes (7,8). Invading transposons are major agents of interspecies gene transfer (27).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these monooxygenases differ not only in their substrate specificity (e.g., hydroxylation of only methoxy or methoxy and ethoxy groups of tert-alkyl ethers) but also in their isotope fractionation, and thus a critical evaluation of two-dimensional (D/H and 13 C/ 12 C) isotope analysis is needed for assessing degradation activities at contaminated sites (5). The best-studied fuel oxygenate monooxygenase for MTBE and ETBE hydroxylation is the cytochrome P450 EthABCD system found in several Gram-positive bacterial strains of the genera Rhodococcus, Gordonia, and Mycobacterium (7,8,9). The corresponding genes are located in the ethRABCD gene cluster encoding an AraC/XylS-type positive transcriptional regulator (ethR), a ferredoxin reductase (ethA), a cytochrome P450 monooxygenase (ethB), a ferredoxin (ethC), and a protein with an unknown function (ethD).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The eth genes cluster was highly conserved in Rhodococcus zopfii IFP 2005 and Mycobacterium sp. IFP 2009, two other strains isolated from activated sludge with capacity similar to that of R. ruber IFP 2001 (Béguin et al 2003), (2) The non-heme alkane hydroxylase of the well-known Pseudomonas putida GPo1 that oxidises MTBE but not TBA after growth on n-octane , but with a low affinity for MTBE (20 mM<Ks<40 mM). These authors showed that the loss of the OCT plasmid resulted in the inability to degrade MTBE.…”
Section: Introductionmentioning
confidence: 99%
“…Adaptation of microbial communities to the presence of xenobiotics in their environment may arise as a result of a combination of different mechanisms, such as an increase in the population size of the organisms that degrade the target xenobiotic, mutations of various kinds (e.g., single nucleotide changes or DNA rearrangements) that result in resistance to or degradation of the target xenobiotic, and acquisition of genetic traits by horizontal gene transfer (Spain and Van Veld 1983). Interestingly, there is an evidence to suggest that genes involved in the degradation of ether fuels might be transferred horizontally between bacteria belonging to the Rhodococcus group that is known to be capable of degrading ACN (Acharya and Desai 1997;Beguin et al 2003;Endo and Watanabe 1989;Kobayashi et al 1990;Langdanhl et al 1996). Although the extent to which each of the adaptive mechanisms contributed to the development of ACNdegrading biofilm has yet to be determined, it is likely that such adaptation selected individual or groups of microorganisms that best suited to tolerate and degrade ACN, and these microorganisms eventually swept over and dominated the microbial community.…”
Section: Discussionmentioning
confidence: 99%